1994
DOI: 10.1055/s-2007-994548
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal and Intracervical Prostaglandin E2For Cervical Ripening: A Doppler Study of Hemodynamic Effects

Abstract: The hemodynamic effects of vaginally and intracervically administered prostaglandin E2 gel were evaluated by pulsed wave color Doppler ultrasound. Twenty term pregnant mothers were recruited. Mothers were randomized to receive either vaginal or intracervical prostaglandin E2 gel. The hemodynamics was assessed by repeated color Doppler velocimetry of the uterine artery and fetal umbilical and middle cerebral arteries; analysis of variance was used to test statistical significance. In the uterine artery a statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that the S/D ratio did not change significantly for the fetal aorta and UA circulation after a single intravaginal dose of prostaglandin E 2 for cervical ripening (15). It has been also demonstrated that the fetal PI remained unchanged both in the umbilical and cerebral vessels after prostaglandin E 2 application (14). In addition, misoprostol, a synthetic analogue of naturally occurring PGE 1 , is being studied for obstetric-and abortion-related uses with its better success rate and less cost (16,17).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that the S/D ratio did not change significantly for the fetal aorta and UA circulation after a single intravaginal dose of prostaglandin E 2 for cervical ripening (15). It has been also demonstrated that the fetal PI remained unchanged both in the umbilical and cerebral vessels after prostaglandin E 2 application (14). In addition, misoprostol, a synthetic analogue of naturally occurring PGE 1 , is being studied for obstetric-and abortion-related uses with its better success rate and less cost (16,17).…”
Section: Discussionmentioning
confidence: 97%
“…There were, however, only a few reports studying the relationship between induction and hemodynamic changes of fetuses. It has been demonstrated that the fetal pulsatility index in the UA and fetal MCA remained unchanged after administration of prostglandin E 2 (12)(13)(14)(15). Recently, prostaglandin E 1 (PGE 1 ) was studied extensively for its better success rate of induction and decreased cost (16,17).…”
mentioning
confidence: 99%
“…We observed a significant increase in the uterine artery resistance after dinoprostone application among those who underwent emergency cesarean delivery for persistent non‐reassuring FHR pattern. There have been a few studies showing increased uterine artery Doppler velocities due to Prostaglandin E2 use, but none of the studies included data about the assessment of abnormal outcome during follow‐up (19–21). Rotmensch et al studied the effect of dinoprostone in post‐term pregnancies on Doppler flow of the umbilical, MCA, and the uterine arteries and they found an increase of only uterine artery RI after dinoprostone (20).…”
Section: Discussionmentioning
confidence: 99%